Effects of fining with different bentonite labels and doses on colloidal stability and colour of a Valpolicella red wine. (18th August 2015) - Dordoni, Roberta; Galasi, Roberta; Colangelo, Donato; De Faveri, Dante Marco; Lambri, Milena
Summary This study addressed four different labels of activated sodium bentonite during the fining of a young Valpolicella red wine. Preliminary tests determined the bentonite dose (0.15, 0.30 or 0.50 g L−1) that would achieve colloidal stability, and this dose was further applied during laboratory‐scale trials. The bentonites were characterised by physico‐chemical parameters, and the effects of the label and dose on the wine colloidal stability, proteins, colour indices and phenolic compounds were measured. The results demonstrated that 0.50 g L−1 for every bentonite label provided colloidal stabilisation without harshly affecting the colour. Unlike to what happens in white wines the least charged bentonite labels were effective at stabilising the red wine colloidal state by partially reducing its protein content. Simultaneously, the most negatively charged clay samples determined the largest depletions on the total polyphenols, anthocyanins, tannins and polymeric pigments. The differentiated action of clays with different surface charge density among white and red wines may be explained by the interaction mediated by positively charged anthocyanins towards either protein or tannin depletion. Although pioneering, these results may move towards the definition of a safe, allergen‐free, and effective adjuvant for colloidal stabilisation targeted to wine type.